Horizontal patchiness of sympagic organisms in the Antarctic fast ice - Kerrie Swadling; Gibson, JAE; Ritz, DA; Peter Nichols (1997)
Patchiness in the horizontal distribution of sympagic organisms was studied at an Antarctic coastal site during autumn. A hierarchical sampling design (nested ANOVA) was used to assess variation in the biota on scales from metres to kilometres. Metazoan abundance, chlorophyll concentration and salinity were measured in 54 sea ice cores. The metazoan fauna was dominated by nauplii of the copepod Paralabidocera antarctica (6 x 104 to 4 x 105 m2). Other copepods present included Stephos longipes, Oncaea curvata, Oithona similis, Ctenocalanus citer, and unidentified harpacticoid copepods. Chlorophyll a concentrations were generally much higher than values recorded at other sites at the same time of the year, reaching a maximum of 78 mg m2. Metazoan abundances did not correlate strongly with chlorophyll or salinity. Significant variability in abundance of P. antarctica and O. similis, and chlorophyll concentration occurred at the scale of kilometres, whereas salinity and other metazoan abundances were not significantly variable at any of the scales examined. Considerable variation was evident at scales of less than one metre.